Cardiac hypertrophy and insulin therapy in a pre-term newborn: is there a relationship? - Guglielmo Salvatori; Giulia Brindisi; Mario Colantonio; Anna Maria Zicari (BMC, 2022)
Abstract Background Hypertrophic cardiomyopathy (HCM) in newborns is a rare condition with heterogeneous etiologies. While the relationship between hyperinsulinism and cardiac hypertrophy (CH) is known, hyperinsulinism has not been reported as cause of HCM. Case presentation We report the case of cardiac hypertrophy (CH) in an Extremely Low Birth Weight (ELBW) infant; this patient underwent insulin therapy after the onset of persistent hyperglycemia due to parenteral nutrition (PN), supporting the hypothesis of a role of iatrogenic hyperinsulinemia in the development of HCM. Conclusions The present case underlines the importance of a close cardiological follow-up in infants undergoing insulin infusion for an alteration in the glucose metabolism.